2010
DOI: 10.1007/s00264-010-1098-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeally irradiated autografts for the treatment of bone tumours: tips and tricks

Abstract: We retrospectively reviewed 107 patients with 108 malignant or locally aggressive bone tumours treated between 1978 and 2009 by extracorporeal irradiation with 300 Gy to eradicate the tumour, and reimplantation of the bone as an orthotopic autograft. Patient subgroups were defined according to resection type. We describe the local recurrence rate, the graft infection rate and the factors affecting graft healing and graft survival. No local recurrences were detected in the irradiated grafts. At fiveyear follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 26 publications
3
37
0
9
Order By: Relevance
“…25 The technique of excision, irradiation and reimplantation has the advantage of being a biological reconstruction with the potential for long-term survival. 26 It is cheap and convenient, but requires the proximity of a radiotherapy department. 27 Only one surgeon is needed and the operating time is much shorter than with the Capanna technique.…”
Section: Discussionmentioning
confidence: 99%
“…25 The technique of excision, irradiation and reimplantation has the advantage of being a biological reconstruction with the potential for long-term survival. 26 It is cheap and convenient, but requires the proximity of a radiotherapy department. 27 Only one surgeon is needed and the operating time is much shorter than with the Capanna technique.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been described in the maxillofacial and orthopedic literature for malignant musculoskeletal tumors, where the involved tumorous bone is resected, irradiated extracorporeally, and reimplanted. 3,6,10,11,15,21,25,32 Recently, long-term studies (mean follow-up range of 45-66 months) indicated no local tumor recurrence at the extracorporeally irradiated skeletal bone. 2,3,6,21 Both animal and in vitro human studies directly comparing autoclaving with irradiation indicated a superior biomechanical profile and better incorporation of the reimplanted bone with irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,10,11,15,21,25,32 Recently, long-term studies (mean follow-up range of 45-66 months) indicated no local tumor recurrence at the extracorporeally irradiated skeletal bone. 2,3,6,21 Both animal and in vitro human studies directly comparing autoclaving with irradiation indicated a superior biomechanical profile and better incorporation of the reimplanted bone with irradiation. 6,7,24 When cadaveric bone flaps are used for implantation, they are irradiated to extremely high doses in the range of 1000-40,000 Gy to destroy antigens as well as infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…Emery et al6) reported that long bone fractures after irradiation in laboratory animals are associated with a high pseudarthrosis rate, delayed union, decreased strength and decreased periosteal osteoblastic proliferation, decreased formation of cartilage and osteoid, and decreased vascularity after irradiation. Another study showed that the frequency of delayed unions for extracorporeally irradiated autografts in rats has been related to the irradiation dose19); 16% at 1 kGy, 24% at 5 kGy, and 100% at 25 kGy. Emery et al7) reported that patients who had anterior vertebrectomy and bone strut grafts fusion for spinal neoplasm with irradiation doses greater than 4000 cGy showed increased pseudarthrosis ( p <0.003).…”
Section: Discussionmentioning
confidence: 99%